Purpura fulminans following hump-nosed pit viper (Hypnale hypnale) envenoming: A rare complication of snakebites. (30th October 2021) - Rathnayaka, R.M.M.K. Namal; Ranathunga, P.E.A. Nishanthi; Kularatne, S.A.M.; Abeywardhana, K.P. Lalith
Abstract: Hump-nosed pit vipers of the genus Hypnale are highly venomous and reputed for the commonest venomous snakebites in Sri Lanka. They frequently cause local manifestations and less commonly cause systemic effects such as acute kidney injury and coagulopathy. There is no antivenom currently available in Sri Lanka for their envenoming. However, more and more complications of Hypnale bites are being recently described. Purpura fulminans, one of the rare complications of snakebites that we report following authentic Hypnale hypnale bite. A 58-year-old female was bitten by a hump-nosed viper and developed bilateral toe gangrenes, ultimately ended up with amputations. She got recovered with loss of toes in both feet for 46 days treatment at hospital. Graphical abstract: Image 1 Highlights: A rare case of describing purpura fulminans in snakebites. First case of describing purpura fulminans in hump-nosed pit viper bites. Patient recovered with loss of toes in both feet. Thrombosis of dermal vessels is the predominant pathology.